2010
DOI: 10.3113/fai.2010.0391
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Plantar Fasciitis Treated with Two Sessions of Radial Extracorporeal Shock Wave Therapy

Abstract: RSWT was successful in the treatment of chronic PF even when only two sessions with 2,000 impulses each were performed 1 week apart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 22 publications
2
54
0
8
Order By: Relevance
“…Longer-term followup data were not sufficient or comparable enough for meta-analysis; however, there have been encouraging results up to 12 months after treatment reported in individual articles. Ibrahim et al [8] found a significant difference in the improvement of VAS heel pain scores at 24 weeks when comparing placebo with ESWT (100% versus 16% success; p \ 0.001) in favor of ESWT. However, there were no other studies with the same outcomes to enable an analysis at this length of followup.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Longer-term followup data were not sufficient or comparable enough for meta-analysis; however, there have been encouraging results up to 12 months after treatment reported in individual articles. Ibrahim et al [8] found a significant difference in the improvement of VAS heel pain scores at 24 weeks when comparing placebo with ESWT (100% versus 16% success; p \ 0.001) in favor of ESWT. However, there were no other studies with the same outcomes to enable an analysis at this length of followup.…”
Section: Discussionmentioning
confidence: 98%
“…7). Three studies contributed to the assessment [6][7][8]. As the data were not continuous, it was deemed more appropriate to discuss the results of the trials individually.…”
Section: Placebo 23mentioning
confidence: 99%
“…In a study of 50 patients by Ibrahim et al, the patients in the treatment group were administered with a total of 2 sessions one week apart of shock waves at [20]. In the placebo group, the VAS scores were observed to have improved by 15.2% at 4 th weeks, 13.5% at 12 th weeks and 17% at 24 th weeks and the RM scores improved by 6.3%, 16.8% and 16.8% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many placebo-controlled clinical studies have been published reporting that ESWT is a successful treatment in the treatment of plantar fasciitis with success rates reaching 94% [5,[10][11][12][13][14][15][16][17]19,20]. However, some researchers have reported that ESWT showed no difference in effect from a placebo in the treatment of plantar fasciitis [6,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation